Maternal and fetal aspects. - Pacheco Romero, José (2015)
It is a fact known to the Peruvians the recent decline in about 30 years of GDP and purchasing power, which brought consequently a deterioration of the socioeconomic and political conditions of the country and food deficit. Thus the calorie deficit was around 35% and 40% protein deficit, tending to worsen 26. Of course, proper nutrition depends not only on purchasing power, but knowledge about food and food that we have. Unfortunately, most of the Peruvian population know about quality and nutritional value of food, and eat diets that are negatively unbalanced.